Elevated Testosterone Reduces Uterine Blood Flow, Spiral Artery Elongation, and Placental Oxygenation in Pregnant Rats. Issue 3 (March 2016) - Gopalakrishnan, Kathirvel; Mishra, Jay S.; Chinnathambi, Vijayakumar; Vincent, Kathleen L.; Patrikeev, Igor; Motamedi, Massoud; Saade, George R.; Hankins, Gary D.; Sathishkumar, Kunju
Abstract : Elevated maternal testosterone levels are shown to cause fetal growth restriction, eventually culminating in sex-specific adult-onset hypertension that is more pronounced in males than in females. In this study, we tested whether uteroplacental and fetoplacental disturbances underlie fetal growth restriction and if these changes vary in male and female placentas. Pregnant Sprague-Dawley rats were injected with vehicle (n=16) or testosterone propionate (0.5 mg/kg per day from gestation day 15–19; n=16). On gestation day 20, we quantified uterine artery blood flow using microultrasound, visualized placental arterial network using x-ray microcomputed tomography, determined fetoplacental hypoxia using pimonidazole and hypoxia-inducible factor-1α, and used Affymetrix array to determine changes in placental expression of genes involved in vascular development. Plasma testosterone levels increased 2-fold in testosterone-injected rats. Placental and fetal weights were lower in rats with elevated testosterone. Uterine artery blood flow was lower, and resistance index was higher in the testosterone group. Radial and spiral artery diameter and length, the number of fetoplacental arterial branches, and umbilical artery diameter were reduced in the testosterone group. In addition, markers of hypoxia in the placentas and fetuses were elevated in the testosterone group. The magnitude of changes in placental vasculature and hypoxia was greater in males than in females and was associated with sex-specific alteration of unique sets of genes involved in angiogenesis and blood vessel morphogenesis. The results demonstrate that elevated testosterone during gestation induces a decrease in uterine arterial blood flow and fetal sex–related uteroplacental vascular changes, which may set the stage for subsequent sex differences in adult-onset diseases. Abstract : Supplemental Digital Content is available in the text.